Respostas cardiorrespiratórias promovidas pela ativação de receptores glutamatérgicos e purinérgicos no núcleo do trato solitário - Fávero, Michele Thaís (2012)
The central nervous system (CNS) has an important role in maintaining the composition and volume of body fluids for the appropriate tissue perfusion. An important area of the CNS that receives cardiorespiratory afferents is the nucleus of the solitary tract (NTS) that has several types of neurotransmitters, includingL-glutamate and adenosine 5'-triphosphate (ATP). Neuroendocrine changes that occur during sodium depletion could change glutamatergi c and purinergic neurotransmissions into the NTS. Thus, in this study, we investigated : 1) the effects of sodium depletion on cardiorespiratory responses before and after injections of L -glutamate and α,β-methyleneadenosine 5′-triphosphate (α,β-methyl ATP, a selective P2X purinergic receptor agonist) into the NTS of unanesthetized and sodium depleted rats; 2) the cardiorespiratory responses of the injection of α,β-methyl ATP before and after the blockade of P2 receptor purinergic antagonist with suramin (non-selective P2 purinergic receptor antagonist) into NTS of unanesthetized and normovolemic rats and 3) to describe the autonomic components involved with the cardiovascular responses after injection of α,β-methyl ATP into the NTS. Male Holtzman rats with a cannula implanted into the NTS and catheters inserted into the femoral artery and vein were used. Ventilation (VE) was measured by whole body plethysmograph method. In relation to objective 1, the cardiorespiratory parameters were measured in normovolemic (before sodium depletion), depleted (24 h after sodium depletion) and repleted rats (two hours after free access to 0.3 M NaCl and water). Sodium depletion was induced by the treatment with the diuretic furosemide (20 mg/kg of body weight) injected subcut aneously (s.c.) followed by 24 h of sodium -deficient diet. Sodium depletion did not modify baseline MAP (104 ± 4 mmHg, vs. normovolemic: 105 ± 4 mmHg) or HR (334 ± 20 bpm, vs. normovolemic: 379 ± 13 bpm) but increased the VE (708 ± 107 ml/min/kg, vs. normovolemic: 478 ± 60 ml/min/kg). This effect was due to increase on tidal volume (VT, 7 ± 0.6 ml/kg, vs. normovolemic: 5 ± 0.4 ml/kg) without effect on the respiratory frequency (fR, 99 ± 8 cpm, vs. normovolemic: 85 ± 6 cpm). In repleted rats, VE did not return to normal level (640 ± 33 ml/min/kg, vs. normovolemic: 478 ± 60 ml/min/kg). Unilateral injections of L-glutamate (1 and 5 nmol/100 nl) into the NTS produced pressor response (17 ± 3 and 36 ± 3 mmHg, respectively, vs. saline: 3 ± 1 mmHg), bradycardia (-130 ± 15 and -169 ± 10 bpm, respectively, vs. saline: -13 ± 6 bpm) and the hyperventilation (233 ± 44 and 495 ± 114 ml/min/kg, respectively, vs. saline: 32 ± 26 ml/min/kg). Sodium depletion reduced pressor responses (4 ± 3 mmHg and 13 ± 4 mmHg, respectively) and hyperventilation (-112 ± 112 and 7 ± 115 ml/min/kg, respectively) and did not change bradycardia (-116 ± 30 and -156 ± 18 bpm, respectively). Unilateral injections of α,β-methyl ATP (2 nmol/100 nl) into the NTS also produced pressor response (36 ± 5 mmHg, vs. saline: 3 ± 1 mmHg), bradycardia (-194 ± 18 bpm, vs. saline: -13 ± 6 bpm) and did not change VE (54 ± 96 ml/min/kg, vs. saline: 32 ± 26 ml/min/kg). Sodium depletion reduced pressor response (24 ± 5 mmHg), VE ( -147 ± 184 ml/min/kg) and did not change bradycardia (-168 ± 22 bpm). In relation to objective 2, the results showed that injection of α,β-methyl ATP (2 nmol/100 nl) into NTS produced pressor response (24 ± 4 mmHg e -187 ± 39 bpm, respectively) and these responses were reduced 15 min after injection of suramin into NTS ipsilateral (13 ± 2 mmHg e -80 ± 18 bpm). Injection of α,β-methyl ATP into NTS produced no significantly change in VE. In relation to objective 3, the results showed that injection of α,β-methyl ATP (2 nmol/100 nl) into NTS promote pressor and bradycardic response (32 ± 5 mmHg and -183 ± 21 bpm). The pre-treatment with the alpha1 -adrenoceptor antagonist prazosin (1 mg/kg bw, i.v.) attenuated the increase in MAP (+10 ± 3 mmHg) without changing the bradycardic response (-192 ± 21 bpm) evoked by injection of α,β-methyl ATP into NTS. The pre-treatment with the cholinergic muscarinic antagonist, methyl-atropine (1 mg/kg bw, i.v.) did not changed the pressor response (+31 ± 6 mmHg) and abolished the bradycardic response (+21 ± 6 bpm) induced by injection of α,β-methyl ATP into the NTS. The results suggest that neuroendocrine changes produced by sodium depletion (increased level of circulating ANG II, aldosterone and the desactivation of the volume receptors and baroreceptors) may change the glutamatergic and purinergic neurotransmissions into the NTS. Furthermore, activation of P2X receptors in the NTS activates both the sympathetic and parasympathetic nervous system to produce pressor and bradycardic responses, respectively, without changing ventilation